Ancient islands or ancient mariners? The cryptic history and voyages of the South Pacific barnacle Rehderella Zevina & Kurshakova, 1973 (Cirripedia: Thoracica: Chthamalidae). Issue 4 (17th December 2022) - Wares, John P; Thiel, Martin; Munizaga, Martin; Rech, Sabine; Carlton, James T
Abstract: We report the first verified DNA barcode data for the tropical chthamalid barnacle Rehderella belyaevi (Zevina & Kurshakova, 1973 ) and place it in phylogenetic and biogeographic context among other lineages of Pacific barnacles. Hitherto found on a few remote but widely separated islands across the South Pacific, R. belyaevi is the sole described species of its genus. Phylogenetic analyses indicate that Nesochthamalus intertextus (Darwin, 1854 ) is its sister taxon and that this taxon pair is nested in a cluster of South Pacific chthamalid taxa. We found that the Pitcairn Is. population includes an admixture of diversity from French Polynesia and Rapa Nui (Easter I.), with those populations being quite divergent. In light of the long history of ocean-going vessel movements in this region, beginning with Polynesian voyagers and the propensity of chthamalid barnacles to occur in biofouling communities, the sequence diversity on Pitcairn is suggestive of ship-borne influence, the more so since the tremendous distances between these islands may preclude natural larval dispersal among them. The true distributional range of Rehderella in the South Pacific is unknown, as shown by our report herein of an undescribed lineage of this genus in French Polynesia based on specimens collected 20 years ago. Furthermore, our discovery that this species occurs on floating plastic debris, a vast amount of which is now present throughout the South Pacific, suggests that the ocean voyages of Rehderella may continue.